Digital Interactive TV and Metadata Future Broadcast Multimedia - Lugmayr, Artur; Niiranen, S.; Kalli, S. (2013)
Future Broadcast Multimedia Arthur Lugmayr, Samuli Niiranen, Seppo Kalli. • metadata definition: syntax and semantic definition of a set of attributes, transaction sets, list of reference data (e.g. values), syntax and notation for construction [100, ...